Monitoring of Some Chemical Changes in Turkish Uslu Monocultivar EVOO During 12 Months of Storage - Ghanbari Shendi, Esmaeil; Ozay, D. Sivri; Ozkaya, M. T.; Ustunel, N. F. (Fakultas Farmasi, Universitas Gadjah Mada, 2018)
In this research, a Turkish olive cultivar named as â€œUsluâ€ locally grown in Akhisar was used for production of monocultivar extra virgin olive oil (EVOO) by using Mobile Olive Oil Processing Unitâ€ (TEM Oliomio 500-2GV, Italy). Olive oil samples were bottled and stored up to 12 months. Some chemical properties such as free fatty acid content, peroxide value, moisture content and UV absorbance value, minor and major components (tocopherols, total phenol compounds and phenolic composition), were determined during storage for 12 months. Chemical parameters such as free fatty acid content, peroxide value of â€œUsluâ€ olive oil samples were in agreement with the trade standards of International Olive Council (IOC).Â Results showed that color values of EVOO changed from green to yellow. UV absorbance values altered during storage. EVOO samples had very low free fatty acidity (0.2%) values which are unusual for commercial olive oils at the end of storage time. Uslu EVOO samples had high content of total phenols (359.33 ppm) and Î±-tocopherol (265.80 ppm). These values decreased approximately 25.37-15.48 % at the end of storage, respectively. Luteolin was the most abundant phenolic compound and its concentration decreased from 289.54 to 257.00ppm during storage. Results showed that tocopherol isomers, total phenols and phenolic compounds content decreased during 12 months storing.